Effects from dayside magnetosphere to distant tail unleashed by a bifurcated, non-reconnecting interplanetary current sheet - Farrugia, C. J.; Lugaz, N.; Wing, S.; Wilson, L. B.; Sibeck, D. J.; Cowley, S. W. H.; Torbert, R. B.; Vasquez, B. J.; Berchem, J. (Frontiers in Physics, 2022)
Global magnetospheric effects resulting from the passage at Earth of large-scale structures have been well studied. The effects of common and short-term features, such as discontinuities and current sheets (CSs), have not been studied in the same depth. Herein we show how a seemingly unremarkable interplanetary feature can cause widespread effects in the magnetosheath-magnetosphere system. The feature was observed by ACE inside an interplanetary coronal mass ejection (CME) on January 10, 2004. It contained (i) a magnetic field dip bounded by directional discontinuities in field and flows, occurring together with (ii) a density peak in what we identify as a bifurcated, non-reconnecting CS. Data from an array of spacecraft in key regions of the magnetosheath/magnetosphere (Geotail, Cluster, Polar, and DMSP) provide context for Wind’s observations of flapping of the distant (R -226 RE) magnetotail. In particular, just before the flapping began, Wind observed a hot and tenuous plasma in a magnetic field structure with enhanced field strength, with the By and Bz components rotating in a fast tailward flow burst. Closer inspection reveals a large flux rope (plasmoid) containing lobe plasma in a tail strongly deflected and twisted by interplanetary non-radial flows and magnetic field By. We try to identify the origin of this ‘precursor to flapping’ by looking at data from the various spacecraft. Working back towards the dayside, we discover a chain of effects which we argue were set in motion by the interplanetary CS and its interaction with the bow shock. These effects include (1) a compression and dilation of the magnetosphere, (2) a local deformation of the postnoon magnetopause, and, (3) at the poleward edge of the oval in an otherwise quiet polar cap flow, a strong (3 km/s) sunward flow burst in a double vortex-like structure flanked by two sets of field-aligned currents. Clearly, an intertwined set of phenomena was occurring at the same time. We learn that multi-spacecraft analysis can give us great insight into the magnetospheric response to transient changes in the solar wind.